2011
DOI: 10.1520/jai103033
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Platelet Reorientation in Zircaloy Studied with Synchrotron Radiation Diffraction

Abstract: Hydrogen ingress into zirconium alloy fuel cladding in light water reactors can degrade cladding performance as a result of the formation of brittle hydrides. In service, hydrides normally precipitate in the circumferential direction and are homogeneously distributed through the cladding thickness in ideal cases. However, temperature and stress gradients in the cladding can promote hydrogen redistribution. This hydrogen redistribution is responsible for the formation of hydride rims, dissolution, and reorienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…the RD data). Very similar bilinear thermal expansion behavior during heating has been observed previously for the δ{111} planes aligned with the edges of hydride platelets in Zircaloy-4 [8,36]; similar to the present study, a higher thermal expansion rate (similar to that of unconstrained hydrides) was observed at elevated temperatures. both the TD and RD δ{111} d-spacings are lower than the value measured at the same temperature during heating, suggesting that the hydrides were under additional compressive strains when precipitation began, although it is also possible that the initial stoichiometry of the precipitating hydride is different [37].…”
Section: Resultssupporting
confidence: 92%
“…the RD data). Very similar bilinear thermal expansion behavior during heating has been observed previously for the δ{111} planes aligned with the edges of hydride platelets in Zircaloy-4 [8,36]; similar to the present study, a higher thermal expansion rate (similar to that of unconstrained hydrides) was observed at elevated temperatures. both the TD and RD δ{111} d-spacings are lower than the value measured at the same temperature during heating, suggesting that the hydrides were under additional compressive strains when precipitation began, although it is also possible that the initial stoichiometry of the precipitating hydride is different [37].…”
Section: Resultssupporting
confidence: 92%
“…The tensile properties of the CSWR Zircaloy-4 sheet were obtained by performing tensile tests at temperatures in the range of 25 to 450 °C. The mechanical response of the Zircaloy-4 sheet after it plastically yields was modeled by power law hardening; the flow parameters were determined from uniaxial tension sample experiments and from studies performed previously using similar materials [18,26,28,[30][31][32][33][34]. The strain-hardening exponent of the sheet used in this study (n = dln/dln = 0.014 at 25 °C, 0.023 at 300 °C, and 0.022 at 400 °C) is significantly smaller than that of standard cladding (n  0.06 at 300 °C) [31].…”
Section: Experimental and Computational Proceduresmentioning
confidence: 99%
“…Although hydride reorientation is influenced by properties inherent to the alloy such as the degree of cold work, grain microstructure, texture, and others [5][6][7][8][9][10], and by parameters related to the specific thermo-mechanical treatments, such as maximum temperature, dwell time at maximum temperature, cooling rate, and number of thermo-mechanical cycles, the critical parameter is the threshold stress (σ th ) [11][12][13][14][15][16][17][18]. Most of the data on the threshold stress for hydride reorientation in zirconium-base alloys available in the literature has been obtained from uniaxial tension tests [6][7][8][16][17][18][19][20][21][22][23][24]. However, during the vacuum drying process, the thin-wall nuclear fuel cladding tubes are subjected to internal gas pressure and/or pellet clad mechanical interaction (PCMI) that create stress biaxiality ratios (σ 2 /σ 1 ) ≥ 0.5, much higher than that for uniaxial tension (σ 2 /σ 1 = 0) [25].…”
Section: Introductionmentioning
confidence: 99%
“…These dislocation loops may be very important in whether the hydrides reorient or not during this transition [27,58e60]. Studies by Colas et al have found threshold stresses for this reorientation [27,58,60,61]. Their results indicate that d precipitates forming under no applied load are elastically strained in compression in both the rolling and transverse directions due to the lower density of hydrides.…”
Section: Hydride Growth and Re-orientationmentioning
confidence: 99%